Self-efficacy and perceived utility as necessary conditions for self-regulated academic learning - Rosário, Pedro; Lourenço, Abílio; Paiva, María Olímpia; Núñez, José Carlos; González Pienda, Julio A.; Valle, Antonio (Anales de Psicología / Annals of Psychology, 2012)
Grounded on the social cognitive perspective, the current investigation aims at evaluating, through a structural equation model, the extent to which school achievement (Portuguese and Math) can be explained by using self-regulated learning strategies and how those self-regulated behaviors can be affected by perceived instrumentality as well as by students’ perceived competence to manage learning strategies adequately. In order to develop the structural equation model the hypothesized learning variables previously referred are supposed to be significantly affected by students’ study time, grade level and school underachievement (number of years failed at school). The EQS model has been developed with a sample of 750 Portuguese students attending compulsory education (12 to 15 years old) randomly selected among a larger group of students from ten different schools. Data confirm the importance of teachers’ using embedded self-regulated strategies in the academic tasks assigned to their students, promoting their transference to other contexts and different academic activities, once this teaching practice will be a privileged way to make learning strategies’ usefulness clear and to ensure the promotion of students’ perceived competence.